2008
DOI: 10.1007/s00213-008-1356-8
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogens as discriminative stimuli in animals: LSD, phenethylamines, and tryptamines

Abstract: Background Although man's first encounters with hallucinogens predate written history, it was not until the rise of the sister disciplines of organic chemistry and pharmacology in the nineteenth century that scientific studies became possible. Mescaline was the first to be isolated and its chemical structure determined. Since then, additional drugs have been recovered from their natural sources and synthetic chemists have contributed many more. Given their profound effects upon human behavior and the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 147 publications
(133 reference statements)
0
50
0
2
Order By: Relevance
“…1). LSD and MDMA do not generalize to the discriminative stimulus effects of PCP in rats (7). The discriminative stimulus effects of PCP were diminished by combination with LSD or MDMA in rats, presumably due to masking effects (7).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…1). LSD and MDMA do not generalize to the discriminative stimulus effects of PCP in rats (7). The discriminative stimulus effects of PCP were diminished by combination with LSD or MDMA in rats, presumably due to masking effects (7).…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have indicated that the activation of 5-HT 2 receptors plays a role in the discriminative stimulus effects of U50,488H, PCP, MDMA, and LSD in animals (7,34). Even though these hallucinogenic drugs in some cases induce similar behavioral phenotypes, each type of drug exerts different discriminative stimulus effects by regulating different receptors and signals (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our molecular and behavioral studies demonstrate that efavirenz has pharmacological properties predictive of psychoactive effects in humans. Although efavirenz interacts with several receptors within a similar range of concentration, several lines of evidence suggest that the psychoactive effects of efavirenz are predominately mediated by activation of the serotonin 5-HT 2A receptor similar to the psychoactive effects of LSD and other related hallucinogens (Fiorella et al, 1995;Winter, 2009). First, efavirenz has partial agonist properties at cloned serotonin 5-HT 2A receptors, which are blocked by antagonists of this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the expression of pro-apoptotic Bax, cytochrome-c and caspase-9 were upregulated at the mRNA and protein level after ICG exposure. 374 ICG-related damage to the retina has long been thought to result in lower visual acuity than expected after surgery. 375,376 For example, a study from Korea showed that indocyanine greenrelated RPE atrophy in an elderly woman resulted in best-corrected visual acuity of 20/63 in the right eye and 20/125 in the left eye.…”
Section: Indocyanine Greenmentioning
confidence: 99%